2016
DOI: 10.1002/ejhf.504
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic incremental role of right ventricular function in acute decompensation of advanced chronic heart failure

Abstract: AimsThe purpose of this study was to evaluate the additional prognostic value of echocardiography in acute decompensation of advanced chronic heart failure (CHF), focusing on right ventricular (RV) dysfunction and its interaction with loading conditions. Few data are available on the prognostic role of echocardiography in acute HF and on the significance of pulmonary hypertension in patients with severe RV failure. Methods and resultsA total of 265 NYHA IV patients admitted for acute decompensation of advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 29 publications
3
49
0
5
Order By: Relevance
“…A fundamental component of right heart distribution system is the right ventricle. It is now largely demonstrated that RV dysfunction is common in HF and that its presence contributes to increased morbidity and mortality RV distribution system . As a matter of fact, the poor prognosis in PH‐HF could not be the direct consequence to the remodelling of the pulmonary circulation, but it could be attributed to the detrimental consequence that PH exerts on the right ventricle.…”
Section: Do the Various Definitions Of Post‐capillary Pulmonary Hypermentioning
confidence: 99%
See 1 more Smart Citation
“…A fundamental component of right heart distribution system is the right ventricle. It is now largely demonstrated that RV dysfunction is common in HF and that its presence contributes to increased morbidity and mortality RV distribution system . As a matter of fact, the poor prognosis in PH‐HF could not be the direct consequence to the remodelling of the pulmonary circulation, but it could be attributed to the detrimental consequence that PH exerts on the right ventricle.…”
Section: Do the Various Definitions Of Post‐capillary Pulmonary Hypermentioning
confidence: 99%
“…Chronic PH induces right ventricular (RV) remodelling and might lead to RV failure, which has been shown to be an important prognostic factor in HF . At the late stage of HF, an elevated PVR has been considered a contraindication to heart transplantation as it may induce RV graft failure .…”
Section: Introductionmentioning
confidence: 99%
“…W zaleceniach podkreśla się, że jest to wskaźnik zależny od funkcji włókien podłużnych mięśnia RV, ale ponieważ objętość wyrzutowa RV w głów-nym stopniu zależy od ich funkcji, to wskaźnik ten dobrze odzwierciedla globalną czynność skurczową RV [16][17][18]. Pomiar nie jest czasochłonny i w mniejszym stopniu (niż powyżej opisywane wskaźniki) zależy od jakości obrazu.…”
Section: Maksymalna Skurczowa Prędkość S'unclassified
“…Так, ее наличие позволяет выявлять среди пациентов с хронической сердечной недостаточ-ностью (ХСН) лиц с крайне неблагоприятным про-гнозом -продолжительностью жизни менее 2 лет [1]. При декомпенсации ХСН наилучшими прогностиче-скими критериями были низкий индекс давления со-кращения ПЖ и высокое расчетное давление в правом предсердии (ПП) [2]. У больных с ХСН с сохраненной фракцией выброса левого желудочка (ФВЛЖ) неза-висимая ассоциация с прогнозом выявлена для дис-функции ПЖ (р <0,001) и систолического давления в легочной артерии (ЛА) (р =0,003), но не для лево-желудочковых показателей [3].…”
unclassified